Para a prosódia do foco em variedades do Português Europeu - Cruz, Marisa (2017)
The present paper examines the prosodic realization of narrow focus in southern varieties of European Portuguese - Algarve (Alg) and Alentejo (Ale) -, in two speech styles (reading and role-play interview). Data were analysed for nuclear pitch accent (NPA) configuration, NPA realization (pitch range), and post-focal behaviour in early focus utterances. The results show that the type of NPA in focused declaratives is more homogeneous across varieties and speech styles than the one used in interrogatives: H*+L in the former; different strategies to express focus in the latter. Early focus statements reveal post-focal subordination of the H+L* pitch accent, realized with a compressed range across varieties.